Análise de polimorfismos em genes de detoxificação e reparo em indivíduos de municípios goianos - Alves, Alessandro Arruda (2017)
In Brazilian agriculture, the State of Goiás is one of the largest producers of corn, beans, cotton, sorghum, sugarcane and soybeans, with 75% of its exports composed of products related to agriculture and minerals. Thus, a large part of the economy of the State of Goiás is focused on rural activities, justifying the intense use of pesticides in the region. These pesticides will be metabolized in the liver in two main phases, the first one of bioactivation converting the original substances into more polar metabolites, through oxidation reduction reactions, hydrogenation and dehalogenation, most of the reactions are made by the cytochrome P450 (CYP) superfamily And the second phase in which conjugation reactions occur, in which metabolites are converted into non-toxic products. Agrochemicals are also known to cause various human health damage, such as cancer, cholinergic syndrome, Parkinson's disease and Alzheimer's as well as cytogenetic changes such as DNA damage and chromosome translocations. Thus, polymorphisms in enzymes acting in the path of detoxification and DNA repair may be important biomarkers of diseases in individuals exposed to pesticides. The present study sequenced 3 regions of the following genes: CYP2E1 (promoter region), CYP1A1 (exon 7) and OGG1 (intron region) of 260 individuals from Goiânia and Aparecida de Goiânia, GO. 20 ml of blood was collected, DNA was extracted using commercial kits and PCR was performed. Subsequently, the amplicons were sequenced by the automated Sanger method and compared to the 1000 Genome project. The population of this study was composed of 159 men and 101 women, mean age of 38 years. A total of 5 SNP's were found in the Goias population, being rs2031922 (change of C> T and frequency of the T allele of 0.05) of the CYP2E1 gene, rs1048943 (change of A> G and frequency of the G allele of 0.1 ) And rs1799814 (change of C> A and frequency of allele A of 0.07) of the CYP1A1 gene and rs1052133 (change of C> G and frequency of allele G of 0.2) and rs293795 (change of A> G and frequency Of the 0.18 T allele) of the OGG1 gene. All loci did not deviate from the Hardy-Weinberg equilibrium, nor was a statistically significant difference between age and genotype composition. The rs1048943 and rs1799814 loci of the CYP1A1 gene showed a moderate disequilibrium linkage and the rs1052133 and rs293795 loci of the OGG1 gene showed a strong disequilibrium linkage. The haplotype inference revealed a frequency of the haplotypes of loci rs1048943 and rs1799814 of A / C = 0.8, G / A = 0.12, A / A = 0.07 of the CYP1A1 gene. The haplotypes of the loci rs293795 and rs1052133 had A / G = 0.07, A / C = 0.8, G / C = 0.13. Due to the important participation in detoxification or DNA repair and relationship with pesticides, SNPs rs2031920 of the CYP2E1 gene, rs1048943 of CYP1A1 and rs1052133 of the OGG1 gene are potential biomarkers of susceptibility to disease development in individuals who have contact with these xenobiotics